Answer:
The right solution is "
".
Step-by-step explanation:
The given inequality is:
⇒ ![-2x>10](https://tex.z-dn.net/?f=-2x%3E10)
By solving the above expression, we get
⇒ ![x >-\frac{10}{2}](https://tex.z-dn.net/?f=x%20%3E-%5Cfrac%7B10%7D%7B2%7D)
⇒ ![x>-5](https://tex.z-dn.net/?f=x%3E-5)
Thus the above is the correct answer.
Answer:
Step-by-step explanation:
Answer:
(2,4)
Step-by-step explanation:
Answer:
J
Step-by-step explanation:
Find the common ratio r of the geometric sequence then multiply a term by r to obtain the next term
r =
=
= - ![\frac{1}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B6%7D)
The next 3 terms are
× -
= - ![\frac{1}{36}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B36%7D)
-
× -
= ![\frac{1}{216}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B216%7D)
× -
= - ![\frac{1}{1296}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B1296%7D)
Answer:
C. x + 6
Step-by-step explanation:
Start by factoring completely the numerator and the denominator.
2x + 12 = 2(x + 6)
x^2 + 7x + 6 = (x + 1)(x + 6)
The only common factor is x + 6, so the GCF is x + 6